Cooperation between The Consumer and Firms as A Determinant of Marketing Innovation: Empirical Study of Portuguese Firms - Moreira, Jacinta; Silva, Maria José Aguilar Madeira (Contemporary Management Research, 2014)
This article analyzes the impact of cooperation with customers and consumers on Portuguese companies’ ability to engage in marketing innovation. To this end, the theoretical framework underlying the study comprises the characterization of marketing innovation and cooperation, especially from the companies’ standpoint of collaboration with customers and consumers, which will support the formulation of the research hypotheses. The hypotheses are tested using secondary data pertaining to the Community Innovation Survey–CIS 2010; logistic regression models will be applied. According to the results, cooperation with customers and consumers is crucial for marketing innovation to occur in companies as companies that cooperate with others show a greater propensity to innovate in marketing. Keywords: Marketing Innovation, Cooperation, Consumer, CIS 2010 To cite this document: Jacinta Moreira and Maria José Aguilar Madeira Silva, "Cooperation between The Consumer and Firms as A Determinant of Marketing Innovation: Empirical Study of Portuguese Firms", Contemporary Management Research, Vol.10, No.3, pp.215-232, 2014. Permanent link to this document: http://dx.doi.org/10.7903/cmr.12370